IDENTIFIKASI ZONA SESAR MENGGUNAKAN PENDEKATAN GEOMORFOLOGI TEKTONIK DAN PEMETAAN GEOLOGI DI DESA BAN, KABUPATEN KARANGASEM, BALI - Ida Bagus Oka Agastya; Putu Diyan Diwyastra; Suryo Hespiantoro (PPSDM Geominerba, 2022)
This study focus on the movement of the fault that caused an earthquake on October 16, 2021 at 03:18:23 WITA with an earthquake magnitude of 4.8 Mw. The epicenter of the earthquake on land was at coordinates 115.45° East Longitude and 8.32° South Latitude with a depth of 10 km. The purpose of this study was to identify the presence of an active fault zone and to determine the fault kinematics in Ban Karangasem. The method used is SRTM DEM Image Analysis, Tectonic Geomorphology Approach, and Geological Mapping. Secondary data collected by GIS (Geographical Information System), and primary data collected by field surveying to observe the existing deformation and topography to determine the geometry and kinematics of an active fault. Focal Mecanism Analysis also used to determine the kinematics active fault, data sources published by BMKG. The results showed there are geological structures in the Buyan Beratan and Batur Purba Formation (Qpvb) and the Agung Volcano Formation (Qhva) in the study area. The geological structure is in the form of shear dan gash fracture, right slip fault, left normal slip fault, and left slip fault. The fault is classified as an active fault and cuts young rock, with an estimated fault zone length of 18 km with 5 fault segments. The existence of this fault zone is influenced by subduction activities in the south of Bali Island between the Eurasian Continental Plate and the Indo-Australian Ocean Plate.